Food and nutrition actions and continuing education in Primary Healthcare: a cross-sectional study Paraíba, 2021 - Micaela de Sousa Menezes; Carla Campos Muniz Medeiros; Danielle Franklin de Carvalho; Ricardo Alves de Olinda; Mônica Oliveira da Silva Simões (Epidemiologia e Serviços de Saúde, 2025)
Abstract Objectives Describe the actions to promote adequate and healthy eating conducted in Primary Care, in addition to presenting the training provided to healthcare professionals when obesity care is offered and its association with the implementation of lines of care and food and nutritional surveillance in municipalities in the state of Paraíba, Brazil. Methods This was a cross-sectional study carried out with health professionals from January to June 2021, in municipalities in Paraíba. Descriptive analysis was performed and, to test the associations, Pearson’s chi-square test and Fisher’s exact test were used, as necessary. Results The Community actions were the most frequent, adopted by teams in 56.1% of cases, followed by group actions that occurred with a frequency of 55.0%. The implementation of the line of care was greater in municipalities with less than 30 thousand inhabitants that carried out permanent education (p-value<0.001). The implementation of food and nutritional surveillance was higher in the total sample in municipalities with 30,000 to 150,000 inhabitants and with less than 30,000 inhabitants (p-value<0.001) who carried out permanent education actions. Conclusion Community and group actions were adopted in Primary Care in Paraíba. Continuing education showed a positive association with the implementation of lines of care and nutritional surveillance, especially in smaller municipalities. These results highlighted the importance of evaluating, monitoring and expanding continuing education initiatives in Paraíba to strengthen food and nutrition actions..